The Responsibility of Transboundary Haze Pollution: The Case of Wildfire in Canada - Gunawan, Yordan; Hafsari, Dhayu Ajeng; Khasanah, Pentanita Uswatun; Arumbinang, Mohammad Hazyar (Universitas Brawijaya, 2024)
Responsibility for losses other countries suffer due to haze pollution is a serious issue. Transboundary haze pollution responsibility is related to the impact of smog pollution in one country and negatively impacts other countries in the vicinity. A country should take responsibility for forest fires out of respect for the country and its citizens. One example is the forest fires in Canada that spread smoke to neighbouring countries. This involves cooperation between countries to reduce the risk of transboundary haze pollution. This article used qualitative descriptive research methods. Qualitative descriptive research methods seek to answer the